2020
DOI: 10.5430/ijfr.v11n2p424
|View full text |Cite
|
Sign up to set email alerts
|

IFRS and Financial Performance: Study in the French Context

Abstract: This article examines the direct and indirect impact of the IFRS mandatory adoption on the financial performance of companies. The structural equation method has been applied to all companies that belong to the CAC All tradable index for the period from 2002 to 2012. By measuring financial performance by three measures, namely the Marris ratio, the Tobin Q and the PER ratio, the results show that the imposition of the international standards has no direct effect on the financial performance, its effect is indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Nwaogwugwu (2020) concluded that the adoption of IFRS did not lead to significant changes in financial statements information in Nigeria. Turki et al (2020) found that there was no direct impact of the implementation of IFRS on the financial ratios of companies in France. On the other hand, the results of this study contradict the results of some previous studies conducted in other countries.…”
Section: Discussionmentioning
confidence: 90%
“…Nwaogwugwu (2020) concluded that the adoption of IFRS did not lead to significant changes in financial statements information in Nigeria. Turki et al (2020) found that there was no direct impact of the implementation of IFRS on the financial ratios of companies in France. On the other hand, the results of this study contradict the results of some previous studies conducted in other countries.…”
Section: Discussionmentioning
confidence: 90%
“…They concluded that the adoption of IFRSs did not lead to higher performance. Turki et al (2020) tested the impact of IFRS on the performance of companies in France based on three financial ratios, namely, Marris ratio, Tobin Q and PER ratio, and found that there was no direct impact of the application of IFRS on the performance of companies and that the impact of the application was indirect through the cost of capital. In Egypt, Hussein and Nounou (2021) suggested that there are no significant differences between IFRS companies and non-IFRS companies for both stock price and stock return ratios.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%